2014
DOI: 10.1021/ac500536w
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Simulation of Ion Concentration Polarization Induced by Nanoporous Membranes in Dual Channel Devices

Abstract: Many microfluidic devices have been utilizing ion concentration polarization (ICP) phenomena by using a permselective, nanoporous membrane with electric fields for a variety of preconcentration applications. However, numerical analyses on the ICP phenomena have not drawn sufficient attention, although they are an intriguing and interdisciplinary research area. In this work, we propose a 2-D model and present numerical simulation results on the ICP, which were obtained by solving three coupled governing equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…It is noted that our previous simulation results of DC-ICP devices offered the same conclusion of the effect of the charge density on ICP being insignificant in low-EPM conditions. 22 To simulate ICP phenomena more accurately, we assumed a high EPM condition (3×) and repeated the simulations under the same electric potential (5 V) and the membrane charge densities of −0.1, −0.25, −0.5, −0.75, and −1.0 mM. Figure 4c shows the distribution of ion concentrations that drops sharply down to 0.1 mM near the membrane, with the lowest concentration at nearly 0.01 mM along the interface between the membrane and the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noted that our previous simulation results of DC-ICP devices offered the same conclusion of the effect of the charge density on ICP being insignificant in low-EPM conditions. 22 To simulate ICP phenomena more accurately, we assumed a high EPM condition (3×) and repeated the simulations under the same electric potential (5 V) and the membrane charge densities of −0.1, −0.25, −0.5, −0.75, and −1.0 mM. Figure 4c shows the distribution of ion concentrations that drops sharply down to 0.1 mM near the membrane, with the lowest concentration at nearly 0.01 mM along the interface between the membrane and the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 In addition, we found that the variation of the EPM of counterions in the nanoporous membrane makes a greater impact on the strength of ICP than the charge density of the membrane. However, DC-ICP devices are unique in that ions are forced to penetrate through the nanoporous membrane, isolating two channels so that it is necessary to study other general models for comprehensive understanding of ICP phenomena.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…12 Among them, pH-tunable biomimetic nanopores, nanosized pores in solid-state membranes modified with pH-regulated polyelectrolyte (PE) brushes, have attracted more attention due to their potential applications in diverse fields, including energy transduction, 1 ionic gates, 2-5 ionic pumps, 6 nanofluidic diodes 7,8 and biosensors, 9 to name a few. Recent studies strongly suggest that as the size of pores is narrowed to the thickness of electric double layer (EDL), unique ion transport properties, not observed in microscale pores, emerge, such as ion selectivity, 13,14 ion concentration polarization (ICP), [15][16][17] and ion concentration rectification (ICR). Recent studies strongly suggest that as the size of pores is narrowed to the thickness of electric double layer (EDL), unique ion transport properties, not observed in microscale pores, emerge, such as ion selectivity, 13,14 ion concentration polarization (ICP), [15][16][17] and ion concentration rectification (ICR).…”
Section: Introductionmentioning
confidence: 99%
“…In order to describe ICP phenomenon above the protruded nanoporous membrane, we established a numerical model which was based on the three-layer model suggested by Rubinstein and Zaltzman 42 for saving computational costs 43, 44 . The computational domain was depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%